The successful containment of a hospital outbreak caused by NDM-1-producing Klebsiella pneumoniae ST307 using active surveillance - Bocanegra Ibarias, Paola; Garza González, Elvira; Padilla Orozco, Magaly; Mendoza Olazarán, Soraya Sarahí; Pérez Alba, Eduardo; Flores Treviño, Samantha Maribel; Garza Ramos, Ulises; Silva Sánchez, Jesús; Camacho Ortiz, Adrián (Public Library of Science, 2019)
The worldwide dissemination of high-risk carbapenemase-producing Klebsiella pneumoniae clones has become a major threat to healthcare facilities. This study describes the successful containment of a hospital outbreak caused by NDM-1-producing K. pneumoniae Sequence Type (ST) 307 using active surveillance. The outbreak began when a patient was transferred from a local hospital. After 48 hours in our hospital, a tracheal aspirate was positive for a meropenem resistant and carbapenemase-producing K. pneumoniae. All patients in the medical intensive care unit (ICU) and the neurology wards were subject to contact precautions. The hospital surfaces and devices, healthcare workers, and patients from these wards were screened by cultures. Fecal swabs were placed into broth and PCR for blaKPC, blaOXA-48, blaIMP, blaVIM, and blaNDM, which were performed directly from the broth after 12 hours. PCRs were also performed on DNA extracted from carbapenemase-producing species from subcultured broths. Five and nine days later, two more patients’ rectal swabs tested positive. Molecular assays identified K. pneumoniae blaNDM-1 onto a 130-kb conjugative plasmid (IncY, IncFIIs, and IncFIIY), ST307. After the three patients were discharged, monitoring continued, and after three weeks with negative results, rectal swabbing ended. In conclusion, it was possible to contain a hospital outbreak caused by NDM-1-producing K. pneumoniae ST307 through epidemiological and microbiological surveillance. With the methodology used, the detection of NDM-type genes in fecal samples was obtained in approximately 15 hours after obtaining the fecal sample.